Perceptual Awareness of Optic Flows Paced Optimally and Non-optimally to Walking Speed. (September 2021) - Motyka, Paweł; Kozłowska, Zuzanna; Litwin, Piotr
Previous research suggests that visual processing depends strongly on locomotor activity and is tuned to optic flows consistent with self-motion speed. Here, we used a binocular rivalry paradigm to investigate whether perceptual access to optic flows depends on their optimality in relation to walking velocity. Participants walked at two different speeds on a treadmill while viewing discrepant visualizations of a virtual tunnel in each eye. We hypothesized that visualizations paced appropriately to the walking speeds will be perceived longer than non optimal (too fast/slow) ones. The presented optic flow speeds were predetermined individually in a task based on matching visual speed to both walking velocities. In addition, perceptual preference for optimal optic flows was expected to increase with proprioceptive ability to detect threshold-level changes in walking speed. Whereas faster (more familiar) optic flows showed enhanced access to awareness during faster compared with slower walking conditions, for slower visual flows, only a nonsignificant tendency for the analogous effect was observed. These effects were not dependent on individual proprioceptive sensitivity. Our findings concur with the emerging view that the velocity of one's locomotion is used to calibrate visual perception of self-motion and extend the scope of reported action effects on visual awareness.